Biological Responses in the Earthworm Eisenia fetida Exposed to Soils near a Typical Lead Acid Battery Plant. Issue 5 (3rd July 2016) - Chao, Gao; Jingbo, Xu; Ji, Li; Zhengtao, Liu
ABSTRACT: There are increasing concerns over the environmental implications involved in battery plant due to the elevated metal concentrations in the surrounding soils. Earthworms are regarded as a model organism for evaluation of terrestrial environmental pollution. The biochemical responses in the earthworms, Eisenia fetida, exposed to polluted soils were investigated. Soil samples at 0, 50, 100, 200, 500 and 1000 m from a battery plant were collected and used to assess the relationship between sampling distance and biochemical responses in E. fetida . Biochemical alterations were carried out on 1, 3, 7 and 14 d of exposure. The metallothionein (MT), malondialdehyde (MDA) and antioxidant enzymes (superoxide dismutase (SOD), catalase (CAT) and peroxidase (POD)) were measured. The results demonstrated that concentrations of heavy metals, especially Pb, decreased sharply with increase in distance, which may be due to the leaching and accumulation of Pb in soil during production processes. The concentrations of MT and MDA increased with exposure (dosage and time), indicating that E. fetida presented dose and time dependence after heavy metal exposure. The activities of SOD and CAT increased after heavy metal induction, while the activity of POD was lower than that of the control group. The SOD, CAT and POD present a cooperative effect for the protection of lipids and enzymes due to the pollution. The soils around the battery plant were polluted with metals giving rise to adverse biological effects.